2014
DOI: 10.1002/jhm.2281
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization in severe sepsis: An integrative review

Abstract: Severe sepsis is a leading cause of long-term morbidity in the United States. Up to half of severe sepsis is treated in non-intensive care unit (ICU) settings, making it applicable to hospitalist practice. Evidence has demonstrated benefits from physical therapy (PT) in myriad conditions; whether PT may benefit severe sepsis patients either within or outside the ICU is unknown. Therefore, we conduct a review of the literature to understand whether early mobilization improves outcomes in patients with severe se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
1
16
0
9
Order By: Relevance
“…In addition, in only one previous trial did researchers follow patients after hospital discharge and assess long-term functional outcomes (25). Furthermore, the authors of multiple systematic reviews have concluded that additional trials are needed to provide more robust evidence to support the efficacy of early PT interventions for patients with acute respiratory failure (14,16,17,27,28).…”
mentioning
confidence: 99%
“…In addition, in only one previous trial did researchers follow patients after hospital discharge and assess long-term functional outcomes (25). Furthermore, the authors of multiple systematic reviews have concluded that additional trials are needed to provide more robust evidence to support the efficacy of early PT interventions for patients with acute respiratory failure (14,16,17,27,28).…”
mentioning
confidence: 99%
“…Existem evidências que o processo inflamatório provocado pela sepse causa disfunção tecidual, como consequência fraqueza muscular global e perda de massa além de miopatia induzida pela sepse 13,37 . Observamos que nossa amostra apresentou queda significativa da qualidade de vida no primeiro mês de alta hospitalar em ambos os grupos, principalmente nos domínios capacidade funcional e aspectos físicos, além de alegar dificuldade em atividades básicas e instrumentais de vida diária 38 .…”
Section: Discussionunclassified
“…O imobilismo e muitas vezes restrição ao leito de pacientes sépticos com internação prolongada, está ligado a desfechos funcionais desfavoráveis, e leva a diversas alterações fisiológicas que promovem descondicionamento por atrofia muscular, redução da síntese proteica, perda de líquidos com alteração de volume sistólico e débito cardíaco, perda óssea e diminuição da sensibilidade à insulina, podendo levar a um maior tempo de internação 13 A realização de exercícios em pacientes críticos internados em ventilação mecânica ajuda a aumentar a tolerância aos exercícios, reduz e previne rigidez articular, dores musculares e preserva a amplitude articular 47 .…”
Section: Discussionunclassified
See 2 more Smart Citations